Asynchronous learning: evaluation of virtual classroom metrics according to the perception of university students - Guillermo Morales-Romero; Adrián Quispe-Andía; César León-Velarde; Irma Aybar-Bellido; Elizabeth Auqui-Ramos; Shirley Quispe-Guía; Carlos Palacios-Huaraca (Institute of Advanced Engineering and Science, 2022)
The process and means that the university offers its students must be efficient and of quality, even more so considering the influence of the quality of educational services on student satisfaction. The objective of this article is to analyze the perception of asynchronous learning according to the evaluation of the virtual classroom metrics, carried out by business administration students, the results will allow to continue improving the teaching-learning process in the virtual context of education higher. The methodology of this study is qualitative at the descriptive level, the validation of the data by Cronbach's Alpha, gave a reliability value of 0.985. The results show us that 73.8% of the students perceive that the virtual classroom improved communication and helped the exchange of information between students and 71.4% indicated that the use of the virtual classroom made them more efficient and secure asynchronous learning activities. According to these results, there is a higher percentage of students who consider that the use of the virtual classroom positively influences their asynchronous learning, therefore, it is proposed to continue improving the skills in the use and appropriation of Technologies of information and communication technology (ICT) in virtual students.